2005
DOI: 10.1007/s00449-005-0022-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear PI controllers for continuous bioreactors using population balance models

Abstract: Continuous bioreactors are critical unit operations in many biological systems, but the unique modeling is very complicated due to the underlying biochemical reactions and the distributed properties of cell population. The scope of this paper considers a popular modeling method for microbial cell cultures by population balance equation models, and the control objective aims to attenuate undesired oscillations appeared in the nonlinear distributed parameter system. In view of pursuing the popular/practical cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…4 Nevertheless, the sustained oscillation or undesired perturbations could obviously deteriorate PI-or PID-controlled nonlinear processes. Recently, Kurtz et al 16 proposed nonlinear controller to attenuate undesired oscillations in microbial cultures described by corpuscular models, and our works 17 showed that the model-based PI control could be directly implemented to stabilize a self-oscillating bioreactor system using a nondistributed nonlinear observer and artificial oscillator. However, the model errors and disturbances could easily degrade the results from our previous works.…”
Section: Introductionmentioning
confidence: 81%
“…4 Nevertheless, the sustained oscillation or undesired perturbations could obviously deteriorate PI-or PID-controlled nonlinear processes. Recently, Kurtz et al 16 proposed nonlinear controller to attenuate undesired oscillations in microbial cultures described by corpuscular models, and our works 17 showed that the model-based PI control could be directly implemented to stabilize a self-oscillating bioreactor system using a nondistributed nonlinear observer and artificial oscillator. However, the model errors and disturbances could easily degrade the results from our previous works.…”
Section: Introductionmentioning
confidence: 81%